MiR-1933-3p is upregulated in skeletal muscles of MuSK+ EAMG mice and affects Impa1 and Mrpl27. (February 2020) - Bogatikov, Evgenii; Lindblad, Ida; Punga, Tanel; Punga, Anna Rostedt
Highlights: We determined the profile of intracellular skeletal muscle microRNAs in MuSK + EAMG mice. Muscle miR-1933-3p and miR-1930-5p were significantly elevated in MuSK + EAMG mice. Transfection of miR-1933-3p into muscle cells reduces the levels of Impa1 and Mrpl27. Abstract: MuSK antibody seropositive (MuSK+) Myasthenia Gravis (MG) typically affects skeletal muscles of the bulbar area, including the omohyoid muscle, causing focal fatigue, weakness and atrophy. The profile of circulating extracellular microRNA (miRNA) is changed in MuSK + MG, but the intracellular miRNA profile in skeletal muscles of MuSK + MG and MuSK + experimental autoimmune MG (EAMG) remains unknown. This study elucidated the intracellular miRNA profile in the omohyoid muscle of mice with MuSK + EAMG. The levels of eleven mouse miRNAs were elevated and two mouse miRNAs were reduced in muscles of MuSK + EAMG mice. Transient expression of miR-1933-3p and miR-1930-5p in mouse muscle (C2C12) cells revealed several downregulated genes, out of which five had predicted binding sites for miR-1933-3p. The mRNA expression of mitochondrial ribosomal protein L27 (Mrpl27) and Inositol monophosphatase I (Impa1) was reduced in miR-1933-3p transfected C2C12 cells compared to control cells (p = 0.032 versus p = 0.020). Further, transient expression of miR-1933-3p reduced Impa1 protein accumulation in C2C12 cells. These findings provide novel insights of dysregulated miRNAs and their intracellular pathways in muscle tissue afflicted with MuSK + EAMG, providing a possible link to mitochondrial dysfunction and muscle atrophy observed in MuSK + MG.